Modelling of nuclear power plant decommissioning financing - Bemš, J; Knápek, J; Králík, T; Hejhal, M; Kubančák, J; Vašíček, J (Radiation protection dosimetry, 2015)
Costs related to the decommissioning of nuclear power plants create a significant financial burden for nuclear power plant operators. This article discusses the various methodologies employed by selected European countries for financing of the liabilities related to the nuclear power plant decommissioning. The article also presents methodology of allocation of future decommissioning costs to the running costs of nuclear power plant in the form of fee imposed on each megawatt hour generated. The application of the methodology is presented in the form of a case study on a new nuclear power plant with installed capacity 1000 MW.
Keywords: Evropa; radiační ochrana; ekonomické modely; Refuse Disposal; radionuklidy; Models, Economic; Time Factors; odpadky - odstraňování; Europe; skládková zařízení; regenerace a remediace životního prostředí; Radioactive Waste; Costs and Cost Analysis; radioaktivní odpad; monitorování radiace; alokace nákladů; Nuclear Power Plants; Cost Allocation; jaderná energie; Radiation Exposure; časové faktory; Radiation Monitoring; Financing, Organized; Radioisotopes; náklady a analýza nákladů; Environmental Restoration and Remediation; financování organizované; jaderné elektrárny; Radiation Protection; Nuclear Energy; Waste Disposal Facilities; radiační expozice